Motor cortex functional connectivity is associated with underlying neurochemistry in ALS. Issue 3 (15th November 2022) - Dey, Avyarthana; Luk, Collin C; Ishaque, Abdullah; Ta, Daniel; Srivastava, Ojas; Krebs, Dennell; Seres, Peter; Hanstock, Chris; Beaulieu, Christian; Korngut, Lawrence; Frayne, Richard; Zinman, Lorne; et al.
Abstract : Objective: To identify structural and neurochemical properties that underlie functional connectivity impairments of the primary motor cortex (PMC) and how these relate to clinical findings in amyotrophic lateral sclerosis (ALS). Methods: 52 patients with ALS and 52 healthy controls, matched for age and sex, were enrolled from 5 centres across Canada for the Canadian ALS Neuroimaging Consortium study. Resting-state functional MRI, diffusion tensor imaging and magnetic resonance spectroscopy data were acquired. Functional connectivity maps, diffusion metrics and neurometabolite ratios were obtained from the analyses of the acquired multimodal data. A clinical assessment of foot tapping (frequency) was performed to examine upper motor neuron function in all participants. Results: Compared with healthy controls, the primary motor cortex in ALS showed reduced functional connectivity with sensory (T=5.21), frontal (T=3.70), temporal (T=3.80), putaminal (T=4.03) and adjacent motor (T=4.60) regions. In the primary motor cortex, N-acetyl aspartate (NAA, a neuronal marker) ratios and diffusion metrics (mean, axial and radial diffusivity, fractional anisotropy (FA)) were altered. Within the ALS cohort, foot tapping frequency correlated with NAA (r=0.347) and white matter FA (r=0.537). NAA levels showed associations with disturbed functional connectivity of the motor cortex. Conclusion: In vivo neurochemistry may represent an effective imaging marker of impaired motor cortex functional connectivity in ALS.